Portable platform for measuring amyloid beta 42/40 ratio via photooxidation-induced fluorescence amplification - Ko, Sanghag; Bae, Hyunjun; Kim, Daewon; Lee, Yeonju; Choi, Isaac; Lee, Dain; Choi, Dong hwan; Kim, Hyung Chul; Sohn, Seo Young; Jeong, Yohan; Chung, Seok; Jung, Young Hee (Royal Society of Chemistry, 2025)
Alzheimer's disease (AD) is a serious health condition that exacerbates with age. Among various AD biomarkers, the measurement of the A beta 42/40 ratio (i.e., ratio of A beta 42 and A beta 40 concentrations) has garnered prominence for the early identification of AD patients and the development of disease-modifying treatments. Approaches such as positron emission tomography examinations and biomarker measurements in cerebrospinal fluid and blood plasma face constraints related to expense and procedural complexity. To address these issues, we developed and evaluated the efficacy of a portable platform for detecting amyloid beta (A beta) 40 and 42 in plasma, utilizing photooxidation-induced fluorescence amplification (PIFA). We conducted a comparative analysis of A beta 42/40 measurements between the PIFA and single-molecule immunoassay (SiMoA) platforms. By measuring 38 cases of subjective cognitive decline (SCD), 24 cases of amnestic mild cognitive impairment (aMCI), and 46 cases of AD dementia samples, we observed a significant difference in A beta 42/40 ratios between the SCD and aMCI groups. The PIFA platform demonstrated an area under the curve compared to that of the SiMoA platform, which is currently the most precise method for A beta 42/40 ratio measurement. Consequently, the PIFA platform presents a viable cost-effective tool for detecting the A beta 42/40 ratio.